The effect of high temperature steam ingestion on aerodynamic performance and stability of a low-speed axial compressor. (March 2020) - Tu, Baofeng; Zhang, Luyao; Fu, Wenjun; Hu, Jun
To investigate the effect of high temperature steam ingestion on the aerodynamic stability of a multistage axial compressor, a two-stage low-speed axial compressor was studied, and full-annulus steady-state and unsteady-state numerical simulations were carried out. The effect of the high temperature steam mass fraction and the distribution of steam at the inlet boundary on the aerodynamic stability of a two-stage low-speed axial compressor was investigated. From the simulation results, we found that high temperature steam ingestion has an adverse effect on the low-speed axial compressor. The larger the steam mass fraction is, the greater the impact of the steam ingestion on the stability boundary and stall margin will be. When the steam mass fraction is equal to 0.35 and 0.7%, the stability margin decreases from 36.07 to 29.72% and 28.05%, respectively. The distribution of steam at the inlet boundary will change the performance and stability. When the steam ingestion range is less than 90°, the steam ingestion area increases and the stability margin will decrease gradually. After 90°, the stability margin is almost unchanged. The difference between the calculated and experimental values of the stability margin reduction caused by steam ingestion is 0.87%. In addition, with the ingestion of high temperature steam, the blockage in the corresponding passages is intensified and the loss is increased, which leads to the occurrence of the stall in advance. It is evident that steam ingestion has a significant impact on compressor stability, ensuring that the steam mass fraction and steam ingestion range are close to the actual value.